Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5395/rde.2014.39.3.180
|View full text |Cite
|
Sign up to set email alerts
|

Enamel pretreatment with Er:YAG laser: effects on the microleakage of fissure sealant in fluorosed teeth

Abstract: ObjectivesThe purpose of this in vitro study was to evaluate the microleakage and penetration of fissure sealant in permanent molar teeth with fluorosis after pretreatment of the occlusal surface.Materials and MethodsA total of 120 third molars with mild dental fluorosis were randomly divided into 6 groups (n = 20). The tooth surfaces were sealed with an unfilled resin fissure sealant (FS) material. The experimental groups included: 1) phosphoric acid etching (AE) + FS (control); 2) AE + One-Step Plus (OS, Bis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…Thus they concluded that Er:YAG laser can be an alternative method before sealant application. 28 Our findings contrast with those of Nahvi and colleagues. 29 They reported significant reduction in micro-leakage with the use of a pre-sealant bonding agent.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus they concluded that Er:YAG laser can be an alternative method before sealant application. 28 Our findings contrast with those of Nahvi and colleagues. 29 They reported significant reduction in micro-leakage with the use of a pre-sealant bonding agent.…”
Section: Discussioncontrasting
confidence: 99%
“…The study by Dumurs et al [22] used Er: YAG laser at a wavelength of 2.94 μm, 2 W power, 120 mJ energy output and 10 Hz frequency. Mahtab et al [45] found no difference in the proportion of microleakage between conventional acid etching and Er: YAG laser surface pretreatment before sealant resin was applied to teeth with fluorosis, where the parameters were 30 mJ, 20 Hz, 6 W initially and 120 mJ, 10 Hz, and 1 W on the enamel margins. Unal et al [46] evaluated the Er:YAG laser as an alternative to acid etching for the application of fissure sealants in pediatric dentistry and found that the Er: YAG laser with 4 W power and 200 mJ energy output resulted in higher microtensile bond strength than the 2 W, 100 mJ Er: YAG laser in permanent teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies recommend preparing cavities with laser treatment to increase resin adhesion to the tooth structure (Yazici et al, 2013;Memarpour et al 2014), or even as an alternative to surface etching (Hossain et al, 2012;Walsh, 2003). However, the effectiveness of this method is controversial (Oznurhan and Olmez, 2013;Tarçin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%